2012
DOI: 10.1177/0011000011432753
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Emotional and Coping Processes

Abstract: Eighteen transgender-identified individuals participated in semi-structured interviews regarding emotional and coping processes throughout their gender transition. The authors used grounded theory to conceptualize and analyze the data. There were three distinct phases through which the participants described emotional and coping experiences: (a) pretransition, (b) during the transition, and (c) posttransition. Five separate themes emerged, including descriptions of coping mechanisms, emotional hardship, lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 40 publications
(56 reference statements)
3
57
1
1
Order By: Relevance
“…Rather than describing all 103 axial codes, we have focused on codes whose names required further explanation and/or codes with concrete clinical implications. Other themes emerging from participants' narratives in this study are described elsewhere (Budge et al, 2010;Budge, Katz-Wise et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rather than describing all 103 axial codes, we have focused on codes whose names required further explanation and/or codes with concrete clinical implications. Other themes emerging from participants' narratives in this study are described elsewhere (Budge et al, 2010;Budge, Katz-Wise et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This research was originally designed to qualitatively investigate transgender individuals' emotional experiences related to gender transitioning (Budge, Katz-Wise et al, 2013). During the interviews and data analysis process, we found that participants' narratives contained many themes of cognitive and interpersonal identity processes related to gender transitioning.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Debido a la importancia del concepto de afrontamiento en psicología de la salud y su aplicación a esta población vulnerable (Budge et al, 2013), contar con un instrumento que evalúe este concepto y que sea validado en población trans constituye un avance importante dentro de los estudios de género. Así, explorar las propiedades psicométricas del CAE en población trans proporcionará información relevante sobre la manera en que este grupo de personas hacen frente a la adversidad, lo que acrecienta el panorama de estudio dentro de los estudios de género y de la psicología.…”
unclassified